2023
DOI: 10.18063/ijb.739
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning boosts three-dimensional bioprinting

Abstract: Three-dimensional (3D) bioprinting is a computer-controlled technology that combines biological factors and bioinks to print an accurate 3D structure in a layer-by-layer fashion. 3D bioprinting is a new tissue engineering technology based on rapid prototyping and additive manufacturing technology, combined with various disciplines. In addition to the problems in in vitro culture process, the bioprinting procedure is also afflicted with a few issues: (1) difficulty in looking for the appropriate bioink to match… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 89 publications
0
3
0
Order By: Relevance
“…Usually, identification of the ideal printing parameters that would ensure both good printability and low cell mortality can be very lackluster, requiring multiple trial and error experiments which cost both money and time. Data-driven machine learning algorithms can impactfully hasten the investigation process for the ideal bioink traits, by delving into vast data collections, accruing particular information based on the desirable properties, and finally conferring an adept predictive model, even before commencing any further in vitro experiments [ 311 , 312 ].…”
Section: Applications Of Bioprinting In Tissue and Organ Regenerationmentioning
confidence: 99%
“…Usually, identification of the ideal printing parameters that would ensure both good printability and low cell mortality can be very lackluster, requiring multiple trial and error experiments which cost both money and time. Data-driven machine learning algorithms can impactfully hasten the investigation process for the ideal bioink traits, by delving into vast data collections, accruing particular information based on the desirable properties, and finally conferring an adept predictive model, even before commencing any further in vitro experiments [ 311 , 312 ].…”
Section: Applications Of Bioprinting In Tissue and Organ Regenerationmentioning
confidence: 99%
“…In the context of 3D-printed hydrogels, CNNs can analyse the printing process and optimise printing parameters. By learning from 3D printing data, CNNs help the user adjust the printing speed, material deposition rate, and other variables to achieve the desired printing outcomes [95]. For example, a deep learning model using CNN was used to generate a model that differentiated between excellent and poor hydrogel prints.…”
Section: Convolutional Neural Networkmentioning
confidence: 99%
“…Recent studies have shown successful applications of machine learning techniques to enhance the 3D printing of biomaterials [11][12][13][14][15]. In these studies, ML has been employed for three main purposes: 1.…”
Section: Introductionmentioning
confidence: 99%